Kajian Tekanan Kerja yang dihadapi oleh Juruukur Bahan dalam Keterlibatan Menguruskan Projek Pembinaan - Mohamad Salimi, Sharul Rizal; Ahmad Latiffi, Aryani (Research in Management of Technology and Business, 2021)
The high demand in the construction industry today has contributed to the increase in work stress to an employee such as a quantity surveyor involved in managing a construction project. The work stress faced by quantity surveyors can affect their job performance, health, and work productivity. Therefore, this study was conducted to examine the level of stress faced by quantity surveyors while performing their duties and identify ways to control and reduce the stress experienced by quantity surveyors in performing their duties. This study was conducted quantitatively by distributing questionnaires to quantity surveyors working in contractor companies with G7 grades in Johor Bahru, Johor. The questionnaires were distributed online using Google Forms. Data findings from the questionnaire were analyzed using the Statistical Package for the Social Sciences (SPSS) version 20. The results of the study found that the level of stress faced by the quantity surveyor is only at moderate stress levels and low stress levels because the total mean score obtained is in the range of 1.00 to 3.79. The results of the study also show that the majority of respondents strongly agree that the most effective way to control and reduce stress is to maintain a good relationship with God such as increasing acts of worship with the highest mean score of 4.79. In conclusion, it is hoped that this study can benefit the construction industry and others so that, the problem of work stress faced by quantity surveyors in the involvement of managing construction projects can be controlled and reduced.